Komunikasi Corporate Social Responsibility Melalui Media Massa Online: Studi Analisis Isi Berita Kegiatan Corporate Social Responsibility PT. PLN (Persero) Distribusi Jawa Tengah dan D.I.Y - Revita Tri Sulastri; Wulan Herdiningsih (Universitas Multimedia Nusantara, 2019)
Intense competition between companies requires companies to be at the forefront and get a positive assessment from the community which leads to an improvement in the company's image. Companies try to please the community and stakeholders by doing positive, innovative things, and showing good achievements to the public. One way is to carry out Corporate Social Responsibility activities and to report activities in the online mass media. The ease of transparency of these business activities is carried out because of the development of communication and information technology that can easily become a bridge of information from the company to the community as well as a means of carrying out the goals or role of Public Relations easily. Reporting on CSR activities can also reveal that the existence of a company is not only to maximize the wealth of the owner, but also to serve the interests of stakeholders such as public, employees, and the government as conveyed by the stakeholder theory. State-owned electricity company PT. PLN in Central Java and Yogyakarta also carries out Corporate Social Responsibility activities and publishes it on online mass media. This research aims to analyze the news contents on the CSR of PT. PLN in Central Java and Yogyakarta published by Tribunjateng.com, by using quantitative content analysis. This descriptive research focuses on the CSR news of the PT PLN and their tendency, which measured by four indicators namely CSR responsibilities, programs, benefits and objectives. The results revealed the tendency of news content on CSR news to discuss the most about CSR Programs with a percentage of 46.4% of 13 news, CSR Responsibility of 32.3%, Benefits of 7.1% and CSR Objectives of 14.3%. Keywords: CSR news, Stakeholder theory, Content analysis, CSR Communications, Public Relations